Age-related changes in connected speech production: evidence from eye-tracking in the culturally adapted picture description task - Lee, Hyeri; Choi, Yoomi; Sung, Jee Eun (Frontiers in Psychology, 2024)
Purpose: Age-related changes in connected speech production remain a subject of debate, yielding inconsistent findings across various tasks and measures. This study aimed to investigate the effects of aging on picture description tasks using two types of pictures: a standardized picture (the Beach picture) and a culturally and linguistically modified picture tailored for Korean speakers (the Han River picture).Method: Twenty-four young adults and 22 older adults participated in two picture description tasks while their eye movements were recorded. Word-level linguistic variables were used to assess informativeness (Correct Information Units per minute) and productivity (noun and verb counts per utterance) of connected speech production. Eye-movement measures were employed to evaluate realtime cognitive processing associated with planning connected speech (pre-speech fixation counts and durations; eye fixations before the speech onset of each utterance).The findings revealed age-related declines in linguistic measures, with older adults exhibiting decreased CIUs per minute and smaller counts of nouns and verbs per utterance. Age-related changes in eye movement measures were evident in that older adults displayed longer pre-speech fixation duration. Unlike younger adults, older adults exhibited higher pre-speech hus, Previous res fixation counts on the Han River picture compared to the Beach picture, suggesting cognitive challenges in performing the task that requires producing more words and detailed descriptions.These results seem to affirm that aging is associated with reduced informativeness and productivity of connected speech, as well as a decline in cognitive processing efficiency.